ASPEK BERPIKIR KRITIS PADA TEKS ULASAN DALAM BUKU TEKS BAHASA INDONESIA KELAS VIII - Nurfaidah Nurfaidah; Azis Azis (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Aspects of Critical Thinking in Review Texts in Class VII Indonesian Language Textbooks. This study aims to describe the critical thinking aspects of interpretation, analysis, evaluation, explanation, proceed to review text reviews in Indonesian language textbooks for class VIII. This study uses a qualitative research type. The data in this study were sourced from Indonesian language textbooks for class VIII SMP. The data collection technique in this study was carried out in two stages, namely: reading carefully the review text and analyzing the review text related to the data included in the required categories. The results of the study reveal. The forms of critical thinking aspects in interpretation are: experiences, situations, events, information. The forms of critical thinking aspects in the analysis are: statements, concepts, descriptions, information. The forms of critical thinking aspects in evaluation are: ideas, situations, mandates. The form of critical thinking aspects at the conclusion are: concepts. The form of the critical thinking aspect of the explanation is: retelling. The form of critical thinking aspects to strengthen oneself, namely: correction.